The pathogenetic basis of correlation secretion thyroids hormons with progress and prognosis chronic obsructive pulmonary disease (COPD) - Matsegora, N. A.; Shpota, O. E. (Journal of Education, Health and Sport, 2018)
We has been studied influence of thyroxine on functional thymalinum-dependence activity of T-cell-bound immunity. It was established that preincubation of T-lympocytes with physiological concentration of thyroxine led to pronounced thymalinum-dependence abolition of receptor field of T-lympocytes modification.The syndrome of low triiodthyronine in patients with COPD is a kind of "factor of complication" of the course of the disease. It is due to the formation of a deeper disruption of reparative regeneration of the bronchial epithelium (including procoagulant and fibrinolytic activity of epithelial cells) and aggravation of immune disbalance.